2018
DOI: 10.26719/2018.24.9.823
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of staffing requirements in primary care in Oman using the Workload Indicators of Staffing Needs method

Abstract: Our objective is to develop national staffing norms to ensure adequate numbers, appropriate skills mix and equitable distribution of professionals working in PHC in Oman using the WISN method. This paper describes the process of formulating the national norms and presents the key findings and some of the limitations. Methods First, a joint team from the Directorate General of Planning and Studies and the Directorate General of Primary Health Care listed all types of primary health care services provided curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…The present study found that midwives’ antenatal care consultation took an average of 22 min (95% CI: 18–26 min) is not significantly different from 25 min estimated from the previous WISN study in Ghana and 20–30 min estimated in a Namibian WISN study [ 35 ]. Additionally, whereas the current study shows that midwives spend 131 min (95% CI: 101–160 min) per supervised vaginal delivery, the WISN study in Ghana, which employed a time-motion observation for this activity, also estimated 152 min, which falls within the confidence limits of the present study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The present study found that midwives’ antenatal care consultation took an average of 22 min (95% CI: 18–26 min) is not significantly different from 25 min estimated from the previous WISN study in Ghana and 20–30 min estimated in a Namibian WISN study [ 35 ]. Additionally, whereas the current study shows that midwives spend 131 min (95% CI: 101–160 min) per supervised vaginal delivery, the WISN study in Ghana, which employed a time-motion observation for this activity, also estimated 152 min, which falls within the confidence limits of the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…To the best of our knowledge, this study is the first attempt to use a cross-sectional survey to estimate activity standards of health service activities across multiple health professions. Previous studies [ 5 , 9 , 10 , 34 , 35 , 36 ] have either been focused on only a few cadres and activities or based on expert group consensus to determine the standard time which the statistical uncertainty in the estimates could not be ascertained. The findings of the study demonstrate that using a cross-sectional survey could yield fairly reliable activity standards suitable for health workforce planning, just as the consensus-based estimates advocated in the WISN methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges identified were data related, as several data sources are needed and in many cases need to be collated [16] to make the projection models as accurate as possible. These models are constantly being revised and scenarios of planning changed [21][22][23]. With the diversity in approaches, different approaches to HRH planning will be appropriate for different jurisdictions…”
Section: Planning Workforce and Training Needsmentioning
confidence: 99%
“…According to the World Health Organization that the method used to analyze the optimal number of medical personnel needs is to use the Work Load Indicator of Staffing Needs method by determining work units and categories of health resources, determining available time, compiling job descriptions and products produced, calculating workload, compile leeway standards, set Human resource requirements [5] .…”
Section: Methodsmentioning
confidence: 99%
“…One way to increase the quantity and quality of adequate health workers is to do HR planning by taking into account human resources needs and workloads of officers. HR planning can be done by calculating using the Workload Indicator Staffing Needs (WISN) [5]. According to the Decree of the Minister of Health of the Republic of Indonesia Number 81 / MENKES / SK / I / 2004 states that the Employment Needs Indicator of Workforce is an indicator that shows the number of human resource needs in health facilities based on workload so that the regulation of the allocation/relocation of health workers will be easier and more rational.…”
Section: Introductionmentioning
confidence: 99%